2022
DOI: 10.3389/fendo.2022.941905
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound characteristics of preoperative central cervical lymph node metastasis in papillary thyroid carcinoma

Abstract: This study evaluated the preoperative diagnostic value of lymph node ultrasonography in distinguishing between benign and malignant central cervical lymph nodes (CCLNs) in patients with papillary thyroid carcinoma (PTC). A total of 176 patients who had PTC with 216 CCLNs (49 benign and 155 malignant) were enrolled in this study and preoperatively imaged by ultrasonography, including conventional ultrasound (US) and contrast-enhanced ultrasound (CEUS). We evaluated the ultrasonography parameters for each lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Several studies show the potential utility of CEUS in the differential diagnosis of benign and malignant thyroid nodules and in the analysis of lymph node involvement ( 21 ). The CEUS parameters including hyper-enhancement, centripetal perfusion, and ring enhancement are related to metastatic lymph nodes ( 15 , 22 ). However, few studies evaluated the association between CEUS features of PTC and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show the potential utility of CEUS in the differential diagnosis of benign and malignant thyroid nodules and in the analysis of lymph node involvement ( 21 ). The CEUS parameters including hyper-enhancement, centripetal perfusion, and ring enhancement are related to metastatic lymph nodes ( 15 , 22 ). However, few studies evaluated the association between CEUS features of PTC and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although PTCs have a favorable prognosis, other scholars contend that the central LNs are the most frequent sites for lymph node metastasis with a high incidence of 13.7%-72.2% ( 14 , 16 , 21 ). Thorough initial dissection with simultaneous dissection of the LN-prRLN is essential to reduce local recurrence and metastasis and avoid significant complication rates by secondary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS, which provides more information about vascularity than conventional US, could reveal the thyroid nodule’s microvasculature and increase the diagnostic accuracy of thyroid nodules ( 12 , 13 ). Our previous studies found that preoperative CEUS characteristics could offer help in predicting central lymph node metastasis in PTCs with coexistent Hashimoto’s thyroiditis and identifying malignant cervical LNs from benign cervical LNs ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Benign SCLNs were more likely to have no tumor history, which was consistent with previous research ( 13 ). For CUS features, well-defined margin, clear boundary, and long/short diameter ≥ 2 shape were commonly observed in benign lesions, but also occasionally seen in malignant lesions ( 14 ). The overlapping of CUS features and clinic data brings some difficulties in the diagnosis of benign and malignant lymph nodes.…”
Section: Discussionmentioning
confidence: 99%